AN OCULAR PERCEPTIVE OF THYROID DISORDERS AND ASSOCIATED FACTORS- A CLINICAL PROSPECTIVE STUDY. - Dr.G.Sireesha; Dr.T.Suchitra; Dr.K.V Praveen kumar; Dr.P.Sushmitha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Thyroid eye disease (TED) also called Graves Orbitopathy, is an autoimmune complex orbital inflammatory disease, which can be sight-threatening, debilitating, and disfiguring. Thyroid disorders, particularly those involving autoimmune etiology such as Graves’ disease, represent a significant public health concern due to their multifactorial impact on patient well-being, particularly through ocular manifestations that can lead to substantial morbidity.